Anti diabetic (AD), stiffness and hardness studies of 2-[4-(Trifluoromethyl) phenyl]-1H-benzimidazole crystals - (TFMPHB) macro and nano crystal. (2020) - Flora, G.; Senthilkannan, K.; Rengarajan, R.; Saravanan, P.
Abstract: TFMPHB full scale and nano precious ones are having significant propel on electronic capacity, stage blending, recurrence conditioning and forced correspondences and different utilities in bio and drug store fields and in enterprises as well. Large scale crystals have smallest significances by appraisal contrasted with nano outline of TFMPHB prepared by mill factory arrangement. The nano form of TFMPHB crystals are of 21 nm respectively, the XRD data reveals the macro crystals are having the formula C14H9F3N2 are of a = 9.2292 Å, b = 9.8117 Å, c = 25.347 Å, orthorhombic with space group Pbca, the macro level SHG (second harmonic generation) NLO (Non linear optical) is higher than that of typical KDP one. Here, both the macro and nano crystals are under studies such as Anti diabetic and hardness profile and reported, TFMPHB are best for electronic sift and for frequency doublers and in gadgets based on influx.